Pre Hospital Management in Emergency Hypoglycemia: A Case Report - Priambodo, Ayu Prawesti; Karisa, Putri; Audly, Tazkia Badliana (Indonesian Journal of Global Health Research, 2024)
The management of hypoglycemia emergencies is a unique challenge for emergency medical services (EMS) providers. Hypoglycemia can occur in many different conditions. If left untreated, it can lead to serious complications, including seizures. The correct management of hypoglycemia in the pre-hospital setting can be a preventative measure against a range of complications that can be associated with hypoglycemia. This study aims to describe cases of prehospital management of hypoglycemic patients with seizures. This study uses a case report approach with an emergency care approach consisting of airway, breathing, circulation, disability and exposure. The case used in this case report is a woman with a history of diabetes mellitus, hypertension and Guillain-Barre Syndrome who experienced emergency hypoglycemia with seizures and decreased consciousness. The case study discusses how pre-hospital care is provided and highlights the pre-hospital management of patients with hypoglycemia associated with seizures. Data were collected by observing the clinical signs and symptoms that appeared, then analyzed to determine the appropriate treatment of hypoglycemia emergencies according to evidence. The results showed that pre-hospital interventions can be pharmacological and non-pharmacological. Recommendations from this case study can be used to consider interventions to be used in prehospital management of patients with hypoglycemia with seizures.